ANALISIS PENYUSUNAN LAPORAN KEUANGAN PADA YAYASAN WACANA KRIDA SUNGAI RAYA KABUPATEN KUBU RAYA - Puspita, Vina; Kristiawati, Endang; Sari, Wilda; Wulandari, Renny (Jurnal Akuntansi, Auditing dan Investasi, 2024)
Financial reports are the result of the accounting process, and are important information for organizations that describe organizational activities in a certain period and for making decisions for the organization. Financial reporting of non-profit entity organizations such as foundations must follow the guidelines for preparing financial reports even though ISAK 35. This research was conducted at the Wacana Krida foundation, Taman Mulia high school, Jalan Sukarno Hatta Arang Limbung, Sungai Raya sub-district, Kubu Raya district, West Kalimantan Province. In this research, the data used is the financial report of the Wacana Krida Sungai Raya Foundation for 2021. Data collection techniques in this research are through direct interviews with relevant sources and knowing how to prepare financial reports at the Wacana Krida Sungai Raya Foundation, documentation by collecting documents in the form of photos, and literature study by learning to read. The results of the research show that the financial reports of the Wacana Krida Sungai Raya Foundation still do not show actual financial reports because the form of financial reports is simple and does not comply with ISAK 35 guidelines.